Mapping the English language competency of local Gayo tourism actors to enhance global competitiveness in the tourism industry - Desi Purnama Sari; Sulistio Ningsih; Ranti Maulya; Rahmaini Fitri (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
English communication skills play a crucial role in shaping service quality and international tourist satisfaction, yet empirical evidence on the linguistic readiness of tourism workers in the Gayo Highlands remains limited. This study examines their English proficiency, with emphasis on speaking and listening as the core competencies required for frontline service interactions. Using a quantitative descriptive design, data were collected from 34 tourism workers and analyzed through descriptive statistics, chi-square tests, and Pearson correlation. The results show that listening and speaking exhibit low to moderate proficiency levels, with both identified as the most challenging skills. The chi-square analysis indicated no significant association between profession and perceived difficulty (χ² = 6.918, p = 0.733), suggesting uniform challenges across occupational groups. A weak negative correlation between work experience and overall proficiency (r = –0.25) further suggests that experience alone does not enhance communicative competence. These findings highlight systemic gaps in English for Tourism preparedness and underscore the need for targeted, needs-based, and simulation-driven training to support service quality and strengthen the competitiveness of rural destinations such as the Gayo Highlands.